Latex intolerance : basic science, epidemiology, and clinical management - Chowdhury, Mahbub M. U; Maibach, Howard I (CRC Press, 2005)
This comprehensive, definitive, and long overdue reference deals specifically with all the manifestations of latex intolerance including irritation, allergic contact dermatitis, and contact urticaria. Each chapter presents the latest research in skin irritation, contact dermatitis, and contact urticaria. The well-illustrated textbook also covers in-depth basic science and clinically relevant practical issues such as the management of latex intolerance and hand dermatitis. Experts with a special interest in this area from the UK, Europe, and the USA provide a balanced international perspective to this first major book dedicated to latex intolerance.
Dermatology : clinical & basic science
Keywords: Hypersensitivity; Dermatitis, Allergic Contact; latex; alergie; alergologie a imunologie; Latex; alergická kontaktní dermatitida; Latex Hypersensitivity; alergie na latex; dermatovenerologie